Evaluation of Butea monosperma & Boerhaavia diffusa In Experimentally Induced Neuropathic Pain - Bhadauria, Manoj Singh; Naidu, M. A. (International Journal of Membrane Science and Technology, 2023)
Aim: The aim of the present investigation is to study the Evaluation of Butea monosperma & Boerhaavia diffusa In Experimentally Induced Neuropathic Pain. Material & Methods: Wistar albino rats weighing between 200-250 grams were selected for the study. The extracts and gallic acid (GA) suspensions were administered to the animals once a day through oral gavage. The suspension of extracts was prepared using 0.5% Na CMC and distilled water. An ideal neuropathic pain model should produce consistent sensory symptoms such as allodynia, hyperalgesia, and spontaneous pain over an extended duration, making it feasible for comprehensive evaluation. The Tibial and Sural Transection Injury model is a surgical technique commonly utilized in experimental settings to induce neuropathic pain in animal subjects, particularly rodents. This model involves the precise transection of the tibial and sural nerves, branches of the sciatic nerve, to elicit neuropathic pain symptoms. In parallel, the surrounding muscular tissue was homogenized with phosphate buffer (pH 7.4) and employed for the determination of myeloperoxidase (MPO) levels. Results: The multifaceted nature of neuropathic pain, coupled with the inadequacies of existing treatments, underscores the importance of exploring alternative interventions, and this study aims to contribute valuable insights to this complex field. Conclusion: These directions are crucial for advancing our understanding, translating findings into clinical applications, and ensuring the sustainability of therapeutic interventions.